(untitled) (Research, Society and Development, 2021)
Although sleep seems to be an inactive state of mind and body, it is closely connected to memory consolidation and cognitive enhancement. Since memory and learning are strongly related, a new field of research develops, which is called after the term of hypnopaedia or sleep-learning. Knowledge about the functions of sleep, along with techniques that are applied on/after a learning task, contributes to the scientific data about brain boosting. Both Slow Wave Sleep and dreaming, affect cognitive functions. During sleeping, learning gets accelerated, the accuracy in data processing rises, unsolved problems get solved, and entrepreneurial ideas come into light. In the following review of researches about sleep and learning, the most important results are presented.